TAFSIR IBNU KATSIR - Ridho Sayyidur Rohmadoni; Erisya Br Lubis; Nabila Putri Madina; Riska Sawitri (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
The study of Qur’anic interpretation continues to develop with the emergence of various methods and approaches in the modern era. Within this diversity, there is a need for tafsir references that are based on the primary sources of Islam. One of the tafsir works grounded in these sources is the Tafsir of Ibn Kathir, which is well known for its tafsir bil ma’thur approach. This approach relies on the main sources of Islam, namely the Qur’an, hadith, and the opinions of the Companions and the Tabi‘in, as the primary basis for interpretation. The method used in this study is a qualitative approach with a library research design. The data are obtained from Tafsir al-Qur’an al-‘Azhim by Ibn Kathir, supported by several relevant secondary literatures in the field of tafsir studies. Previous studies generally focus on Ibn Kathir’s method as a form of tafsir bil ma’thur based on the Qur’an, hadith, and the opinions of the Tabi‘in. However, this study does not only examine the method but also analyzes its relevance within the context of modern tafsir. In conclusion, Ibn Kathir’s tafsir has made a significant contribution to the study of Qur’anic interpretation, particularly in preserving the authenticity of narration-based interpretation. It remains highly relevant as a foundational reference for understanding the Qur’an. The method not only strengthens textual understanding but also provides a solid scholarly foundation for the development of tafsir studies in the modern era.